Audit Energi Pemakaian Air Conditioning (AC) Di Gedung Dinas Pekerjaan Umum Kab. Ketapang Propinsi Kalimantan Barat - Lukman, Arif (ELKHA : Jurnal Teknik Elektro, 2018)
Abstractâ€“Goverment Building Pekerjaan Umum Office of Ketapang District, West Kalimantan is one of government office buildings into categorizedÂ  of office buildings that use air conditioning. To implement one of the government's policy that is to save electricity energy consumption in government building, it must be known Intensity of Energy Consumption in the building, Preliminary Energy Audit Result in Public Service Office Building of Kab. Ketapang shows the value of Energy Consumption Intensity (IKE) of 198.13 kWH / (m ^ 2.year) and belongs to the category of government building with air conditioning with energy efficient enough.To improve the category of energy saving savings, a Detailed Energy Audit should be performed. Detailed Energy Audit Result, through the measurement data analysis step, the search for energy saving opportunities analysis of energy saving opportunities resulted some recommendations that must be done by the Office of Public Works of Kab. Ketapang in order to improve the category of energy-efficient usage. The results of the Detailed Energy Audit improve the category of energy use in Public Works Office to be efficient with the value of Energy Consumption Intensity (IKE) 156.83 kWH / (m2.year)And savings programs that are made include in energy savings program at no cost and with low cost.